Genome information processing by the INO80 chromatin remodeler positions nucleosomes - Elisa Oberbeckmann (Nature Portfolio, 2021)
DNA sequence preferences or statistical positioning of histones has not explained genomic patterns of nucleosome organisation in vivo. Here, the authors establish DNA shape/mechanics as key elements that have evolved together with binding sites of DNA sequence-specific barriers so that such information directs nucleosome positioning by chromatin remodelers.